Implementation of Khiyar Aib in the Sale and Purchase of Wooden Beam from the Perspective of a Compilation of Sharia Economic Law (Case Study in Southeast Padangsidimpuan District) - Fani Pratiwi; Ahmad Zuhri (Universitas KH. Abdul Chalim Mojokerto, 2025)
The study aims to evaluate the application of khiyar aib in wooden block buying and selling transactions. Khiyar means choice, which is the right to choose the best option among several choices. Khiyar aib is the right of the buyer to cancel the transaction and return the goods if the goods are defective. This type of research is empirical legal research with a population consisting of all Panglong in Padangsidimpuan Tenggara District. The research samples are Panglong Jati Raya, Panglong Berlian Jaya, and Panglong Mandiri Lestari. Based on interviews with the owners of the three Panglongs, it was found that none of the Panglongs applied khiyar aib in the practice of buying and selling, even though the owner was a Muslim. As regulated in the Compilation of Sharia Economic Law, in Book II Chapter X, and in Law Number 8 of 1999 concerning the obligations of business actors and consumer rights. The application of khiyar aib should be an important part of the practice of buying and selling. The results of the study indicate a discrepancy between legal theory and field practice in the area.